2007
DOI: 10.1117/12.737885
|View full text |Cite
|
Sign up to set email alerts
|

A catheter-based near-infrared scanning spectroscopy system for imaging lipid-rich plaques in human coronary arteries in vivo

Abstract: Although heart disease remains the leading cause of death in the industrialized world, there is still no method, even under cardiac catheterization, to reliably identify those atherosclerotic lesions most likely to lead to heart attack and death. These lesions, which are often non-stenotic, are frequently comprised of a necrotic, lipid-rich core overlaid with a thin fibrous cap infiltrated with inflammatory cells. InfraReDx has developed a scanning, near-infrared, optical-fiberbased, spectroscopic cardiac cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The first validation study of NIRS, performed in 126 coronary artery segments from 51 autopsy hearts, showed that NIRS could detect with high accuracy (0.80; 95% CI: 0.76-0.85) lipid cores with circumferential extent >60 o located in the superficial plaque (cap thickness <450µm). 66 In this study, which resulted in the first Food and Drug Administration (FDA) diagnostic label claim for lipid core plaque, plaque composition from histology was correlated with the block chemogram in NIRS which displays the probability of the presence of lipid tissue in a 2mm block of the coronary artery. These data were re-analysed by Kang et al 67 who also performed IVUS imaging and focused on the efficacy of the two modalities in assessing the phenotype of the plaque.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The first validation study of NIRS, performed in 126 coronary artery segments from 51 autopsy hearts, showed that NIRS could detect with high accuracy (0.80; 95% CI: 0.76-0.85) lipid cores with circumferential extent >60 o located in the superficial plaque (cap thickness <450µm). 66 In this study, which resulted in the first Food and Drug Administration (FDA) diagnostic label claim for lipid core plaque, plaque composition from histology was correlated with the block chemogram in NIRS which displays the probability of the presence of lipid tissue in a 2mm block of the coronary artery. These data were re-analysed by Kang et al 67 who also performed IVUS imaging and focused on the efficacy of the two modalities in assessing the phenotype of the plaque.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…A low sensitivity (30%) in this study was reported that was attributed to the limited efficacy of NIRS in detecting fibroatheromas with small necrotic cores, while the false positive NIRS estimations were related to the increased lipid component seen in lesions classified as pathological intimal thickening. Two more recent reports took advantage of the data collected in the study of Gardner et al 66 to examine the efficacy of NIRS in detecting plaque morphology: in the study of Puri et al 68 NIRS was able to detect fibroatheromas with a moderate accuracy (c-index: 0.71) while Inaba et al 69 examined the efficacy of this modality in detecting TCFA -which however were only 10 in this dataset -and showed that a maximum lipid core burden index in a 4mm segment≥323 was able to identify TCFA with an excellent accuracy (area under the curve, AUC: 0.84, Supplementary table 4).…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Near infrared reflection spectroscopy (NIRS) is an intravascular catheter-based technique that utilizes optical absorption to detect lipid-core lesions. It lacks depth resolution, however, and cannot locate the position of the lipid-core relative to the lumen boundary [13]. By combining NIRS with IVUS, morphological imaging is added to lipid detection, but the amount and the location of the lipid relative to the lumen remains unknown [14].…”
Section: Introductionmentioning
confidence: 99%